Revision of the Labeonine Genus Sinocrossocheilus (Teleostei: Cyprinidae) from South China - Yuan, Le-Yang; Zhang, E; Huang, Yan-Fei (Zootaxa, 2008)
Sinocrossocheilus was recently diagnosed by Su et al. (2003) as consisting of nine species, i.e. S. bamaensis, S. guizhouensis, S. liuchengensis, S. longibullus, S. tridentis, S. microstomatus, S. nigrovittatus, S. labiatus, and S. papillolabrus. It is actually a catch-all genus that is composed of some species misidentified from Pseudocrossocheilus and Hongshuia. Sinocrossocheilus is here redefined based mainly on the details of the lower lip morphology; it is easily separated from all other Asian Labeonini genera in possessing a lower lip with its median lobe modified into a densely papillated, greatly protruded, crescentic fold and a papillose, slightly protruded, triangular fleshy pad which is posteriorly continuous with the mental region. Two species are recognized in this genus: S. guizhouensis and S. labiatus. Detailed redescriptions are given for the two species. All remaining species do not fit with the new definition of Sinocrossocheilus; six species, i.e. S. papillolabrus, S. nigrovittatus, S. bamaensis, S. longibullus, S. liuchengensis, and S. tridentis, should be moved to Pseudocrossocheilus and S. microstomatus to Hongshuia.